2016
DOI: 10.1590/1678-4499.330
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth-promoting bacteria associated with nitrogen fertilization at topdressing in popcorn agronomic performance

Abstract: The variance analysis showed significant effects (p < 0.05) of inoculation (Londrina environment) and N rates (both environments) only for grain yield. There was no inoculation effect in the grain yield when inoculants were applied together with N-fertilization at topdressing. In the absence of N-fertilization at topdressing, the inoculants Masterfix L. and UEL promoted higher grain yield as compared to the uninoculated plants, with resulting increases of 13.21 and 26.61% in yield, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 23 publications
(30 reference statements)
2
15
0
8
Order By: Relevance
“…In this sense, when nitrogen is xed in the form of ammonium, the nitrifying bacteria in soil turn ammonium into nitrites, but they are rapidly converted into nitrates that can then be taken up by the seedlings [11]. Oscillations in all nitrogen-form concentrations (ammonium, nitrite, and nitrate) in treatments GB and B re ect the bacterial activity and their role in nitrogen cycling [36,37], which is consistent with the bacterial titers found across time (Figure 2). Moreover, these results are supported by a previous study, where it was shown that while nitrogen is xed as ammonium in the soil, nitrates are available for plant uptake ultimately, thanks to bacterial metabolism [11].…”
Section: Ammonium Nitrite and Nitrate Concentration And L Sphaericmentioning
confidence: 99%
“…In this sense, when nitrogen is xed in the form of ammonium, the nitrifying bacteria in soil turn ammonium into nitrites, but they are rapidly converted into nitrates that can then be taken up by the seedlings [11]. Oscillations in all nitrogen-form concentrations (ammonium, nitrite, and nitrate) in treatments GB and B re ect the bacterial activity and their role in nitrogen cycling [36,37], which is consistent with the bacterial titers found across time (Figure 2). Moreover, these results are supported by a previous study, where it was shown that while nitrogen is xed as ammonium in the soil, nitrates are available for plant uptake ultimately, thanks to bacterial metabolism [11].…”
Section: Ammonium Nitrite and Nitrate Concentration And L Sphaericmentioning
confidence: 99%
“…The use of plant growth promoting bacteria (PGPB) is a promising alternative with low environmental impact to increase the efficiency of use of mineral fertilizers, including phosphate, providing high cost-effective yields (Spolaor et al, 2016). The PGPB promote plant growth due to various mechanisms such as biosynthesis of phytohormones and secondary metabolites (Duca et al, 2014;Tahir et al, 2017), biological nitrogen fixation (Li et al, 2017), induction of resistance to biotic stresses (phytopathogen biocontrol) and abiotic stresses (drought and salinity) (Yan et al, 2016;Takishita et al, 2018) production of siderophores metal accumulator (Ali et al, 2014) and soil nutrient solubilization such as phosphorus and potassium (Gupta et al, 2015;Shen et al, 2016;Patel and Archana, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria of the genus Azospirillum brasilense stand out among the PGPB's, mainly in the biological nitrogen fixation (BNF) (SPOLAOR et al, 2016). Bacteria of this genus when inoculated can stimulate the growth by multiple mechanisms, including the improvement in nitrogen nutrition, hormonal synthesis, and ameliorate biotic and abiotic stresses (BASHAN e DE-BASHAN, 2010), consequently increasing root growth, favoring root absorption of water and nutrients (MILLÉO e CRISTÓFOLI, 2016, MORAIS et al, 2016, MUMBACH et al, 2017.…”
Section: Introductionmentioning
confidence: 99%